Increased Otolin-1 in Serum as a Potential Biomarker for Idiopathic Benign Paroxysmal Positional Vertigo Episodes - Wu, Yunqin; Han, Weiwei; Yan, Wang; Lu, Xiaoxiong; Zhou, Min; Li, Li; Guan, Qiongfeng; Fan, Zhenyi (Frontiers in Neurology, 2020)
Objective: Otolin-1, a main specific otoconia matrix protein, passes through the labyrinth-blood barrier and is detectable in peripheral blood. Serum otolin-1 levels differ between patients with benign paroxysmal positional vertigo (BPPV) and healthy controls and are significantly age-related, increasing in healthy controls with age, suggesting that serum otolin-1 levels reflect otolith status. The aim of this study was to determine whether otolin-1 levels change during vertigo episodes in patients with BPPV and whether any change is specific and sensitive enough for BPPV episodes. Method: Patients diagnosed with de novo idiopathic BPPV during an acute episode were included in the study from May 2017 to May 2018. Blood samples were drawn before patients were treated with canalith-repositioning maneuvers. Serum otolin-1 levels were compared between 78 patients and 121 age- and sex-matched healthy individuals. Results: There were no significant differences between the groups in the age distribution, sex ratio, body mass index, clinical history, routine blood parameters, or total protein, albumin, uric acid, creatinine, blood urea nitrogen and lipid profiles (P > 0.05). Serum levels of otolin-1 were significantly higher in BPPV patients than in healthy controls (P < 0.001). Receiver operating characteristic analysis revealed that a serum otolin-1 value of 299.45 pg/ml was the optimal cut-off value to discriminate patients with BPPV from healthy controls (area under the curve 0.757, 95% CI 0.687~0.826) with a sensitivity of 67.9% and a specificity of 72.7%. Conclusion: Serum levels of otolin-1 may be a potential biomarker for BPPV episodes.